Enzymatic Profile and Antibiotic Sensitivity of Some Vibrio and Aeromonas Strains - Al-Dagal, Mosffer M.; Bazaraa, Wael A. (Fishery Technology, 2025)
API-ZYM system and antibiotic sensitivity assay were used to characterize twelve strains of Vibrio and three strains of Aeromonas, each belonging to different species. APIZYM showed that all tested strains exhibited negative activity for a-galactosidase, P-glucuronidase, a-mannosidase and cc-flucosidase. All strains expressed positive activities for alkaline phosphatase, esterase (C4), esterase lipase (C8), leucine arylamidase, acid phosphatase, and naphthol AS-BI phosphohydrdase. p-glucosidase activity was a characteristic of the three Aeromonas strains. Also, Aeromonas strains as well as V. damsela gave very high N-acetyl P-glucosamidase activities. Aeromonas hydrophila, A. trota and V. hollisae were susceptible to all 9 tested antibiotics, and ClO and C30 were active against all tested strains. API-ZYM system and antibiotic susceptibility profile gave additional information that can help in identifying and separating very close species of Vibrio and Aeromonas.